Molecular Mechanisms Underlying the Inhibition of Proliferation and Differentiation by Florfenicol in P19 Stem Cells: Transcriptome Analysis - Hu, Dongfang; Zhang, Bin; Suo, Yu; Li, Zhiyue; Wan, Zhishuai; Zhao, Weihua; Chen, Lingli; Yin, Zhihong; Ning, Hongmei; Ge, Yaming; Li, Weiguo (Frontiers in Pharmacology, 2022)
Florfenicol (FLO), which is widely used in veterinary clinic and aquaculture, can disrupt the protein synthesis of bacteria and mitochondria and thus lead to anti-bacteria and toxic effects in plants, insects, and mammals. FLO was found to repress chicken embryonic development and induce early embryonic death previously, but the underlying mechanism is not fully understood. Clarifying the mechanism of FLO-induced embryonic toxicity is important to the research and development of new drugs and the rational use of FLO to ensure human and animal health and ecological safety. In this study, the effects of FLO on the pluripotency, proliferation, and differentiation were investigated in P19 stem cells (P19SCs). We also identified differentially expressed genes (DEGs) and performed bioinformatics analysis to obtain hub genes and conducted some functional analysis. FLO inhibited the proliferation and pluripotency of P19SCs and repressed the formation of embryoid bodies derived from P19SCs. A total of 2,396 DEGs were identified using RNA-Seq in FLO-treated P19SCs, and these genes were significantly enriched in biological processes such as angiogenesis, embryonic organ development, and morphogenesis of organs. Kyoto encyclopedia of genes and genomes-based pathway analysis also showed that five relevant pathways, especially the canonical Wnt pathway, were engaged in FLO-induced toxicity of pluripotent stem cells. We further analyzed modules and hub genes and found the involvement of ubiquitin-mediated proteolysis, DNA replication, and cell cycle machinery in regulating the pluripotency and proliferation of FLO-treated P19SCs. In summary, our data suggested that FLO disrupted signaling transduction of pathways especially canonical Wnt pathway and further inhibited the expression of target genes involved in regulating DNA replication, cell cycle, and pluripotency. This phenomenon led to the inhibition of proliferation and differentiation in FLO-treated P19SCs. However, further experiments are required to validate our findings and elucidate the potential mechanisms underlying FLO-induced embryonic toxicity.